2018
DOI: 10.1007/s11154-018-9446-3
|View full text |Cite
|
Sign up to set email alerts
|

Not quite type 1 or type 2, what now? Review of monogenic, mitochondrial, and syndromic diabetes

Abstract: Diabetes mellitus is a heterogeneous group of conditions defined by resultant chronic hyperglycemia. Given the increasing prevalence of diabetes mellitus and the increasing understanding of genetic etiologies, we present a broad review of rare genetic forms of diabetes that have differing diagnostic and/or treatment implications from type 1 and type 2 diabetes. Advances in understanding the genotype-phenotype associations in these rare forms of diabetes offer clinically available examples of evolving precision… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 134 publications
0
16
1
1
Order By: Relevance
“…Monogenic forms of diabetes are due to highly penetrant single gene mutations and present across a clinical spectrum that includes MODY, mitochondrial diabetes and genetic syndromes that include diabetes as part of their clinical presentation 5 . Genetic variants of at least 14 known genes cause MODY through pancreatic beta cell dysfunction that leads to hyperglycaemia (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Monogenic forms of diabetes are due to highly penetrant single gene mutations and present across a clinical spectrum that includes MODY, mitochondrial diabetes and genetic syndromes that include diabetes as part of their clinical presentation 5 . Genetic variants of at least 14 known genes cause MODY through pancreatic beta cell dysfunction that leads to hyperglycaemia (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…One of the first direct studies of human islets from an individual with a heterozygous missense variant in the HNF1A locus confirmed that loss-of-function variants of HNF1A lead to insulin-insufficient diabetes not through a significant loss of beta-cell mass but rather by impacting beta-cell transcriptional regulatory networks, resulting in the impairment of beta-cell pathways that are needed for a normal insulin response to glucose [22]. Heterozygous mutations of HNF1A that cause diabetes were first identified in 1996, and more than 400 different mutations have since been described [23]. These mutations include missense and nonsense mutations, insertions and duplications, deletions, insertion/deletions, promoter region mutations, and splice site mutations [24].…”
Section: Discussionmentioning
confidence: 99%
“…T1DM and T2DM are polygenic disorders, that is multiple genes contribute to their development [11,12]. Rare forms of diabetes mellitus (about 1% of cases) are single-gene disorders leading to beta cell or other defects [13].…”
Section: Genetics Of Diabetes Mellitusmentioning
confidence: 99%